2017
DOI: 10.1155/2017/7567958
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Transplantation following Partial Hepatectomy: A New Concept to Promote Liver Regeneration—Systematic Review of the Literature Focused on Experimental Studies in Rodent Models

Abstract: Mesenchymal stem cells (MSCs) are an attractive source for regenerative medicine because they are easily accessible through minimally invasive methods and have the potential to enhance liver regeneration (LG) and improve liver function, following partial hepatectomy (PH) and acute or chronic liver injury. A systematic review of the literature was conducted for articles published up to September 1st, 2016, using the MEDLINE database. The keywords that were used in various combinations were as follows: “Mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 120 publications
(275 reference statements)
1
10
0
Order By: Relevance
“…Hepatocyte growth factor (HGF) and oncostatin M have been used to successfully induce human BMSCs and human UCB-MSCs to differentiate into hepatocyte-like cells [160]. Hepatocyte-like cells have been derived from BMSCs [161], ADSCs [41,42], UCB-MSCs [43], and placenta-derived MSCs (PDSCs) [44] via appropriate culture conditions, including co-culture with hepatocytes on 2D or 3D scaffolds [142], floating culture, or treatment with serum collected from rats after partial hepatectomy [162]. Liver reconstruction using differentiated MSCs has only been demonstrated in the animal models, although recently, a phase II trial showed that transplantation of differentiated autologous MSCs could be used as a potential clinical treatment for liver cirrhosis [14].…”
Section: Msc-based Regenerative Medicinementioning
confidence: 99%
“…Hepatocyte growth factor (HGF) and oncostatin M have been used to successfully induce human BMSCs and human UCB-MSCs to differentiate into hepatocyte-like cells [160]. Hepatocyte-like cells have been derived from BMSCs [161], ADSCs [41,42], UCB-MSCs [43], and placenta-derived MSCs (PDSCs) [44] via appropriate culture conditions, including co-culture with hepatocytes on 2D or 3D scaffolds [142], floating culture, or treatment with serum collected from rats after partial hepatectomy [162]. Liver reconstruction using differentiated MSCs has only been demonstrated in the animal models, although recently, a phase II trial showed that transplantation of differentiated autologous MSCs could be used as a potential clinical treatment for liver cirrhosis [14].…”
Section: Msc-based Regenerative Medicinementioning
confidence: 99%
“…Clinical trials have confirmed the curative effect of MSCs on liver diseases [ 15 , 16 ]. Previous studies proved that, in the models of PHx, infusion of MSCs increased the expressions of HGF, IL-6, and IL-10 and activated the IL-6-STAT3 pathway, thus improving the ability of LR [ 17 19 ]. However, the mechanisms of MSCs in improving LR after PHx remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Such transplantation has overall complications of 38%. Another ALPPS technique associating liver partition and vein portal ligation for staged hepatectomy has an insufficient percentage of regrowth of liver remnants [38, 40, 41].…”
Section: Current Liver Failure Treatmentsmentioning
confidence: 99%